Heat transfer handbook - Bejan, Adrian, 1948-; Kraus, Allan D (New York : J. Wiley, 2003)
Accompanying CD-ROM contains the NIST Thermodynamic and Transport Properties of Pure Fluids Database: Version 5.0 which provides computer formulations with the most up-to-date values for thermophysical properties of fluids and materials
t r / R. T. Jacobsen, E. W. Lemmon, S. G. Penoncello, Z. Shan, N. T. Wright r / M. M. Yovanovich, E. E. Marotta r / Yogendra Joshi, Wataru Nakayama r / Michael F. Modest r / M. A. Kedzierski, J. C. Chato, T. J. Rabas r / Jose L. Lage r / R. M. Manglik r / Jay M. Ochterbeck r / Andrew N. Smith, Pamela M. Norris r t
Includes bibliographical references and index
CD : CD-ROM to accompany heat transfer handbook
System requirements: IBM PC or compatible computer; Windows 95 or later; Internet Explorer 4.1 or later, Netscape 5.0 or later, or a browser capable of reading HTML files
Keywords: Heat -- Transmission -- Handbooks, manuals, etc